The BBIBP-CorV inactivated COVID-19 vaccine induces robust and persistent humoral responses to SARS-CoV-2 nucleocapsid, besides spike protein in healthy adults - Wang, Qinjin; Ning, Jie; Chen, Ying; Li, Bin; Shi, Liang; He, Taojun; Zhang, Fang; Chen, Xingchi; Zhai, Aixia; Wu, Chao (Frontiers in Microbiology, 2022)
Vaccination is one of the best ways to control the severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) epidemic. Among the various SARS-CoV-2 vaccines approved for use, the BBIBP-CorV inactivated vaccine has been widely used in 93 countries. In order to understand deeply the protective mechanism of inactivated vaccine, which retains all antigenic components of live virus, the analysis of humoral responses triggered by multiple proteins is necessary. In this research, antibody responses were generated with 6 selected recombinant proteins and 68 overlapping peptides that completely covered SARS-CoV-2 nucleocapsid (N) protein in 254 healthy volunteers vaccinated with BBIBP-CorV. As a result, antibody responses to the receptor binding domain (RBD), N, and non-structural protein 8 (NSP8) were induced following immunization by BBIBP-CorV. The antibody responses detected in donors after the 2nd dose vaccination can be maintained for about 6 months. Moreover, specific antibody levels can be restored after the boosting vaccination measured by ELISA. Furthermore, the level of SARS-CoV-2 specific IgG response is independent of age and gender. Moreover, N391-408 was identified as a dominant peptide after vaccination of BBIBP-CorV through peptide screening. Understanding the overview of humoral reactivity of the vaccine will contribute to further research on the protective mechanism of the SARS-CoV-2 inactivated vaccine and provide potential biomarkers for the related application of inactivated vaccine.